2008
DOI: 10.1152/ajpendo.00350.2007
|View full text |Cite
|
Sign up to set email alerts
|

Reduced adiposity and improved insulin sensitivity in obese mice with antisense suppression of 4E-BP2 expression

Abstract: S. Reduced adiposity and improved insulin sensitivity in obese mice with antisense suppression of 4E-BP2 expression. Am J Physiol Endocrinol Metab 294: E530-E539, 2008. First published January 15, 2008 doi:10.1152/ajpendo.00350.2007To investigate the possible role of eukaryotic initiation factor 4E-binding protein-2 (4E-BP2) in metabolism and energy homeostasis, high-fat diet-induced obese mice were treated with a 4E-BP2-specific antisense oligonucleotide (ASO) or a control 4E-BP2 ASO at a dose of 25 mg/kg bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…The degradation of several amino acids and metabolites (e.g., for choline, isoleucine, leucine, tyrosine and valine, Table 1) illustrated the request for TCA substrates. Interestingly, both lipid and glucose homeostasis were correlated in biochips with an induction of the insulin pathway, consistently with literature reports (Stephen et al, 1991;Yu et al, 2008). Thus, lipid metabolism was related to gene PI3KR controlling ACACA and FASN (upregulated and inducing lipogenesis) and controlling PDE3B (upregulated and repressing lipolysis).…”
Section: Mechanistic Interpretation Of the Effects Of Microfluidic Cusupporting
confidence: 85%
“…The degradation of several amino acids and metabolites (e.g., for choline, isoleucine, leucine, tyrosine and valine, Table 1) illustrated the request for TCA substrates. Interestingly, both lipid and glucose homeostasis were correlated in biochips with an induction of the insulin pathway, consistently with literature reports (Stephen et al, 1991;Yu et al, 2008). Thus, lipid metabolism was related to gene PI3KR controlling ACACA and FASN (upregulated and inducing lipogenesis) and controlling PDE3B (upregulated and repressing lipolysis).…”
Section: Mechanistic Interpretation Of the Effects Of Microfluidic Cusupporting
confidence: 85%
“…Moreover, 4E-BP1 gene knockout studies in mice have also revealed a reduction in body fat content (51). Reduction in the levels of the 4E-BP2 isoform by the antisense oligonucleotide treatment of obese mice lowered body fat content associated with a reduction in liver lipogenic (fatty acid synthase) and gluconeogenic (glucose-6-phosphatase and phosphoenolpyruvate carboxykinase) gene expression (57). In agreement with our results, Baquet et al (3) reported that amino acids exerted no effect on malonyl-CoA concentrations in incubated hepatocytes in the absence of glucose, whereas lipogenesis was induced at high concentration of glucose and amino acids, suggesting that glucose is the principal regulator of ACC phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…Eight-week-old male C57BL/6J mice were fed HFD ad libitum, received saline vehicle, 15 mg/kg TIP47 ASO (low dose), 50 mg/kg TIP47 ASO (high dose), or control ASO via intraperitoneal injection twice a week for 4 wk, and they continued on HFD throughout the treatment. Chimeric second-generation ASOs were synthesized by ISIS Pharmaceuticals (Carlsbad, CA) and formulated in PBS (10,16,23,30,33). TIP47 ASO, ISIS 409003 (5=-CACAGTGTTGTCTAGGGCCT-3=), is a 20-mer phosphorothioate oligonucleotide complementary to the mRNA for mouse TIP47, and has 2=-O-methoxyethyl-modified ribonucleosides (2=-MOE) at the 3=-and 5=-ends with 2=-deoxynucleosides in between.…”
Section: Methodsmentioning
confidence: 99%